Effects of NH4+-N: NO3−-N ratio on growth, nutrient uptake and production of blueberry (Vaccinium spp.) under soilless culture - Anwar, Ali; Zheng, Junming; Chen, Chunfeng; Chen, Mengqing; Xue, Yanxu; Wang, Jinmiao; Su, Wei; Chen, Riyuan; Song, Shiwei (Frontiers in Plant Science, 2024)
Blueberry (Vaccinium corymbosum) is a crucial economically significant small pulp shrub that prefers to grow on a soilless culture. For soilless culture, nutritional management remains typically vital for blueberry production. However, the effect of different nutritional treatments on blueberry growth and production is largely unknown. This study was designed to investigate to formulate a specific nutritional treatment for blueberry. The results showed that NH4 + -N: NO3 --N ratios significantly affected the growth, nutrient uptake, physiological characteristics, and flowering, as well as the fruiting characteristics of blueberry plants. The number of shoots and top projection area was increased considerably 25:75 treatment. In contrast, 50:50 treatment promotes the plant height, shoot length and stem thickness increase chlorophyll contents, photosynthetic capacity, and contents of P, Ca, and Mg in leaves. 50:50 treatment promotes the flowering, fruiting rate and prolongs the flowering period in blueberries. The maximum soluble sugar was noted in 25:75, while starch contents were maximum in 50:50 treatment. The treatments 100:0 and 75:25 regulate the entire flowering stage earlier and accelerate the development process from flower to fruit. Notably, NH4 + -N: NO3 --N ratios; 50:50 treatment significantly promotes plant growth, nutrient uptake, chlorophyll contents, photosynthetic capacity and fruits setting rate in blueberry plants. These findings suggested that NH4 + -N: NO3 --N ratios; 50:50 is the most appropriate treatment that significantly promotes vegetative growth and enhances production in blueberry plants. This study provides valuable information for improved blueberry production under a controlled environment.